Perkahwinan dan keluarga dalam masyarakat Cam - Fatimah Abdullah,; Mohamad Zain Musa,; Farid Mat Zain, (Universiti Kebangsaan Malaysia, 2010)
Family is an important institution in the formation of a society. In traditional society, family functions as a driving force in economic, social, education and religion. Its members work together or help each other in productive activities, along with educating children in matters relating to the good life skills or religious matters. Although work activities are divided according to gender, all family members and relatives provide each other their mutual assistance, especially during sad moments of distress or death or happy occasions such as marriage. This is not surprising because many family members are living in or near the same village. Current relationship based on traditional family ties are eroding due to modernization followed by urbanization of traditional society. Migration of young people to urban areas to participate in city activities which are of new work patterns has changed patterns of marriage and family relationship in the traditional society. In view of the above description, this article tries to analyse matters relating to patterns of marriage and family relationship in Cam society. Do the patterns of marriage and family in the said community has changed its nature from formerly of endogamy to exogamy marriage? Are there any changes in the family structure and relationship within members of the communityt? Are there any other factors other than those mentioned above which influence these changes. Data presented in this article is based on the research that has been crried out in Cam community in Malaysia and Cambodia